2019
DOI: 10.3390/cancers11111819
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Hepatitis B Virus in Patients with Multiple Myeloma

Abstract: Reactivation of hepatitis B virus (HBV) is a well-known complication in patients with hematological malignancies during or after cytotoxic chemotherapy. If the initiation of antiviral therapy is delayed in patients with HBV reactivation, these patients can develop severe hepatitis and may die of fulminant hepatitis. The preventive strategy for HBV reactivation in patients with malignant lymphoma has already been established based on some prospective studies. As there was an increased number of novel agents bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
(164 reference statements)
0
4
0
Order By: Relevance
“…Therefore, it is likely that this patient achieved HBsAg clearance by combined treatment with bortezomib and entecavir, rather than spontaneous clearance. However, some studies have shown that about 20% of the patients develop HBV reactivation 2 years after initiation of bortezomib treatment, [23] even in patients with resolved HBV infection. [1] Therefore, it remains to be seen whether HBV clearance will be maintained in this patient in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that this patient achieved HBsAg clearance by combined treatment with bortezomib and entecavir, rather than spontaneous clearance. However, some studies have shown that about 20% of the patients develop HBV reactivation 2 years after initiation of bortezomib treatment, [23] even in patients with resolved HBV infection. [1] Therefore, it remains to be seen whether HBV clearance will be maintained in this patient in the future.…”
Section: Discussionmentioning
confidence: 99%
“…HBV reactivation can cause severe hepatitis and lead to fatal fulminant hepatitis. Antiviral prophylaxis from initiation of MM therapy is recommended and monitoring HBV markers is crucial for older MM HBV-positive patients ( 88 ).…”
Section: Treatment Choice and Dose Intensitymentioning
confidence: 99%
“…This Special Issue includes two reviews describing the complications associated with MM [14,15]. The reactivation of hepatitis B virus (HBV) during or after cytotoxic chemotherapy is a well-known complication in patients with hematological malignancies.…”
mentioning
confidence: 99%
“…There is a preventive strategy for HBV reactivation in patients with malignant lymphoma; however, it is yet to be established in patients with MM. On reviewing the Japanese nationwide retrospective survey of HBV reactivation in MM patients, Tsukune et al found that HBV reactivation in MM patients is not rare and that ASCT should be considered as a risk factor [14]. Approximately 20% of MM patients show HBV reactivation 2 years after the initiation of therapy, unlike malignant lymphoma.…”
mentioning
confidence: 99%